2011
DOI: 10.1109/tim.2010.2089190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Errors in ToF Range Imaging With Dual-Frequency Modulation

Abstract: Abstract-Range imaging is a technology that utilizes an amplitude-modulated light source and gain-modulated image sensor to simultaneously produce distance and intensity data for all pixels of the sensor. The precision of such a system is, in part, dependent on the modulation frequency. There is typically a tradeoff between precision and maximum unambiguous range. Research has shown that, by taking two measurements at different modulation frequencies, the unambiguous range can be extended without compromising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 10 publications
2
32
0
Order By: Relevance
“…This is because Q (z)| z=u k = 0 (see (12)). Hence the null space of the polynomial contains the decoupled phase information for the different paths.…”
Section: Closed Form Solution For Retrievingmentioning
confidence: 99%
“…This is because Q (z)| z=u k = 0 (see (12)). Hence the null space of the polynomial contains the decoupled phase information for the different paths.…”
Section: Closed Form Solution For Retrievingmentioning
confidence: 99%
“…Sub-centimetre acquisition requires sampling at rates of 0.1 Hz or lower. Range disambiguation has been implemented [16,17] with little loss of precision. The field of view of the system is limited only by the optical hardware.…”
Section: Resultsmentioning
confidence: 99%
“…Parallel work by the authors (for example [15,17]) provided a theoretical framework to select optimum frequencies within the achievable system bandwidth.…”
mentioning
confidence: 99%
“…Research has shown that, by taking two measurements at different modulation frequencies, the unambiguous range can be extended without compromising distance precision. In [10], an efficient method for combining the two distance measurements obtained using different modulation frequencies are presented and the behavior of the method in the presence of noise has been investigated to determine the expected error rate.…”
Section: Introductionmentioning
confidence: 99%